Case Report: Novel variants in the MYD88 gene (c.104T>C, c.141G>C) in a patient with recurrent abscesses as a cause of type 68 immunodeficiency - Buianova, Anastasiia A.; Ivanov, Artem A.; Belova, Vera A.; Samitova, Alina F.; Kulichenko, Tatiana V.; Vasiliadis, Iuliia A.; Korostin, Dmitriy O.; Lashkova, Yulia S. (Frontiers in Immunology, 2025)
BackgroundPrimary immunodeficiencies (PIDs) comprise a heterogeneous group of disorders characterized by defects in the immune system, predisposing patients to recurrent and severe infections. Type 68 immunodeficiency, caused by biallelic pathogenic variants in MYD88, is rare; to date, at least 26 affected individuals have been reported in the literature, several of whom belong to the same families. This condition typically presents in early childhood with recurrent severe bacterial infections (SBIs), often accompanied by an absent or attenuated inflammatory response.Case presentationWe report a 3-month-old male patient admitted with multiple SBIs, including left-sided abscessing pyelonephritis, pyogenic liver abscess, and septic pneumonia complicated by tension pneumothorax. Initial immunological screening revealed normal leukocyte counts, immunoglobulin levels, lymphocyte subpopulations, and TREC (T-cell receptor excision circle)/KREC (kappa-deleting recombination excision circles) copy numbers. Congenital urinary tract anomalies were excluded. Despite clinical improvement, the patient subsequently developed a cold abscess of the cervical lymph node due to Staphylococcus aureus. Whole-exome sequencing identified two novel compound-heterozygous missense variants in MYD88 (p.Leu35Pro and p.Trp47Cys), both located in the death domain. In silico analysis suggested potential disruption of α-helical structure and MyD88–MyD88/IRAK4 interactions. Sanger sequencing confirmed parental heterozygosity, establishing the diagnosis of type 68 immunodeficiency. Prophylactic antibiotic therapy was initiated, and no further SBIs occurred during 8 months of follow-up.ConclusionThis report expands the genetic spectrum of immunodeficiency 68 by identifying novel MYD88 mutations. Our findings highlight the value of genetic testing in severe, recurrent bacterial infections, irrespective of conventional laboratory results, and demonstrate improved outcomes achievable with modern management.